Effect of race distance on muscle oxygenation in short-track speed skating - Hesford, C. M.; Laing, S.; Cardinale, M.; Cooper, C. E. (Medicine & Science in Sports & Exercise, 2013)
Purpose: Previous work identified an asymmetry in tissue desaturation changes in the left and right quadriceps muscles during on-ice skating at maximal speed in males. The effect of changing race distance on the magnitude of desaturation or leg asymmetry is unknown.